Elastic thermoelectric sponge for pressure-induced enhancement of power generation. (August 2020) - Kim, Jungwon; Bae, Eun Jin; Kang, Young Hun; Lee, Changjin; Cho, Song Yun
Abstract: In this study, a stretchable and elastic thermoelectric (TE) generator with high durability is fabricated and various TE properties are measured and calculated while the compressive pressure is applied to the TE generator. For the elastic TE generator, porous TE sponges are prepared by coating a sponge with single-walled carbon nanotube ink; their TE properties are then systematically measured depending on external strain on the sponge. The TE properties of the porous TE sponge, such as electrical conductivity, power factor, and zT value, increase when compressive strain is increased from 0 to 80% via a controlled change in pore size and density. In addition, p - and n -type TE sponges for the TE sponge generator are prepared easily by simple molecular doping. The maximum output power of the TE sponge generator with 8 p - n pairs is dramatically increased from 0.17 to 2.09 μW at a temperature difference of 55 K under compressive strain of 0 to 80%. These experimental results correspond well with the output power calculated as a function of strain. This elastic and compressive TE material has the potential to be applied in various new TE applications, especially for stretchable and flexible heat sources. Graphical abstract: Elastic and compressible thermoelectric sponge material. Image 1 Highlights: Thermoelectric (TE) sponge coated with single-walled carbon nanotubes is prepared for high compressibility and durability. The TE properties of the porous TE sponge are enhanced by increased compressive strain. The generating performance of the TE sponge generator is dramatically improved with compressive strain.